FORMULASI DAN EVALUASI KRIM VITAMIN E DENGAN VARIASI EMOLIEN - Pritaningtyas, Nazifa Wulan; Putri, Alayya Adistia; Manik, Adelia Margareta; Gintoro, Atilla Dian Dewanti; Elsandi, Elsa; Febrianto, Yahya (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Skin health and aesthetics are becoming a major focus in modern society’s lifestyle, with issues such as dehydration, premature aging, and hyperpigmentation due to UV exposure and pollution. The skin, as the largest organ, requires protection from the harmful effects of sunlight, and the use of sunscreen and skincare products containing vitamin E is becoming increasingly important. This study aims to explore the formulation of vitamin E cream with various emollients to improve product quality and effectiveness. The methodology used includes the creation of cream formulas and evaluation through organoleptic, homogeneity, pH, spreadability, viscosity, and preference tests. The results showed that all three cream formulas met the established standards, with appropriate pH and good homogeneity. The preference test showed varying preferences, providing insight into the development of innovative skincare products. This study is expected to provide solutions for consumers who want effective and environmentally friendly skincare products